2015
DOI: 10.1021/acs.jpcc.5b00588
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Decomposition of the Fullerene Precursor C60H21F9 Deposited on Graphite

Abstract: Specially fluorinated polycyclic aromatic hydrocarbons (F-PAHs) are of interest as precursors for transition metal catalyzed CVD growth of chiral-index pure singlewalled carbon nanotubes as well as for the rational synthesis of fullerenes. Laser desorption/ ionization of a prototypical F-PAH has recently been shown to lead to C 60 via a sequence of regioselective intramolecular cyclodehydrofluorination steps: C 60 H on graphite under UHV conditions toward exploring the extent to which such intramolecular dehyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…In previous work focusing on the thermal stability of solid C 60 H 21 F 9 , we have demonstrated that up to three of these sequential HFelimination steps can already be induced on-surface simply by heating. 3 Therefore, it is possible that, besides unimolecular fragmentation in gas the phase, on-surface reactions (e.g., as mediated by a previous laser pulse) could also be contributing to the fullerene anion signals observed here. Specifically, recombination of smaller polycyclic fragments either on-surface or in the high density region of the desorption plume might be involved.…”
Section: ■ Computational Methodsmentioning
confidence: 88%
See 1 more Smart Citation
“…In previous work focusing on the thermal stability of solid C 60 H 21 F 9 , we have demonstrated that up to three of these sequential HFelimination steps can already be induced on-surface simply by heating. 3 Therefore, it is possible that, besides unimolecular fragmentation in gas the phase, on-surface reactions (e.g., as mediated by a previous laser pulse) could also be contributing to the fullerene anion signals observed here. Specifically, recombination of smaller polycyclic fragments either on-surface or in the high density region of the desorption plume might be involved.…”
Section: ■ Computational Methodsmentioning
confidence: 88%
“…We have recently shown that energization by electron-impact can be used for this purpose. 3 More conventionally, the transformation is activated thermally, e.g., by flash vacuum pyrolysis (in the gas phase) or laser-induced desorption or by heating precursors on (catalytically active) surfaces under ultrahigh vacuum conditions. 4,5 When heating appropriately designed quasiplanar PAH adsorbates on atomically clean flat surfaces, a sequence of such thermally activated on-surface cyclodehydrogenations can lead to increasing curvature and associated strain sufficient to cause carbonaceous caps to form.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Furthermore, after cyclodehydrogenation on a catalyst surface, the respective seed molecules can be elongated a multi‐thousands fold during the SWCNT growth, necessitating only milligram amounts of the respective precursor molecules for the multi‐gram or even kilogram scale production! Taking into account that the present state‐of‐the‐art of MS‐based deposition allows depositing of up to 1 μg of the sample , the gram scale SWCNTs production does not appear to be elusive anymore. In general, the presented synthetic strategy can be further extended to the synthesis of SWCNT precursors for many other chiralities by utilizing various building blocks and other alternative cores.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of high‐molecular weight such precursors cannot be deposited by molecular beam epitaxy without remarkable decomposition. Nevertheless these difficulties can be overcome by using ion beam deposition . In contrast to molecular beam deposition, mass spectrometric deposition allows not only to deposit extra‐large precursors, but also to perform a post synthetic “purification” of the sample .…”
Section: Surface‐assisted Synthesis Of Swcntsmentioning
confidence: 99%
See 1 more Smart Citation